Analiza wzorców zachowań konsumentów w okresie przemian gospodarczych - Michalcewicz, Małgorzata (Analysis of Patterns of Consumers Behavior in the Period of Economic Changes, 2006)
The process of restructuring Polish economy towards market system caused several changes in commerce and service structure. Between 1991 and 2001 there was an increase in number of nutritive shops, but a share of specialist shops decreased. In the 20th century consumer behavior was a subject of survey. Consumers usually have a lot of alternative solutions to choose from. The findings seem to depend on degree in that a presentation of something satisfies waiting, which can be shaped through several factors under or behind control of a vendor.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 93-99